TREATMENT POSSIBILITY FOR AAA OF THE VISCERAL BRANCHES REGION - Utikal, Petr; Kocher, Martin; Koutna, Jirina; Bachleda, Petr; Drac, Petr; Cerna, Marie; Buriankova, Eva; Herman, Jiri (Biomedical papers, 2005)
The authors describe a promising abdominal aortic aneurysm treatment - a combined endovascular/surgical approach - used in two cases of aneurysm taking the aortic visceral branches region.
Keywords: Aorta/Aneurysms/Morphology/Repair/Endovascular/Stent-graft/Visceral branches/Revascularisation/Combined